Pengaruh Kualitas Pelayanan Terhadap Kepuasan Penumpang KMP. Tongkol di Pelabuhan Ujung-Kamal PT. ASDP Indonesia Ferry (Persero) Cabang Surabaya - Narti, Narti; Setiono, Benny Agus; Hardjono, Hardjono (Universitas Hang Tuah, 2020)
Service is an attempt to provide assistance or assistance to others, both in the form, material or non-material so that the person can overcome the problem itself. Based on the phenomenon that occurred at PT. ASDP Indonesia Ferry (Persero) Surabaya branch in observations made by the author found that the facts in the field or precisely in KMP. Tongkol quality of services provided is not good it is seen from the lack of seasts, cleanliness of the bathroom, and lack of hospitality from employees. The study uses quantitative methods is a study by obtaining data in the form of respondets, namely KMP. Tongkol data collection techniques using questionnaire and interview methods with KMP. Tongkol. From the results of the research that has been done it can be concluded that, the results of the validity test are valid, the reliability test is reliable, the hypothesis test and the simple linear regression test. It can be seen from the service of employees when serving passengers in buying tickets, very kind and friendly in their attitude and speech, the employees are also alert when a passenger experiences difficulty in parking their vehicle.